2008
DOI: 10.1136/tc.2007.024281
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness of behavioural interventions to prevent smoking among children and youth

Abstract: Objectives: To evaluate the long-term effectiveness of recent behavioural interventions in the prevention of cigarette use among children and youth and to compare the effectiveness of different school-based, communitybased and multisectorial intervention strategies. Methods: A structured search of databases and a manual search of reference lists was conducted. Randomised controlled trials published in English or German between August 2001 and August 2006 targeting youths up to 18 years of age were assessed ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 57 publications
1
37
0
8
Order By: Relevance
“…For example, reviewing 56 RCTs, Foxcroft et al (2003) found only limited evidence for long-term effects (>3 years) of adolescent alcohol prevention programs, among them Life Skills programs. Similarly, based on 35 evaluation studies on youth tobacco prevention programs with follow-ups conducted 12 to 120 months after baseline assessment, Müller-Riemenschneider et al (2008) identified only moderate evidence that behavioral interventions affected smoking. For interventions within the school context, evidence was inconclusive.…”
Section: Introductionmentioning
confidence: 98%
“…For example, reviewing 56 RCTs, Foxcroft et al (2003) found only limited evidence for long-term effects (>3 years) of adolescent alcohol prevention programs, among them Life Skills programs. Similarly, based on 35 evaluation studies on youth tobacco prevention programs with follow-ups conducted 12 to 120 months after baseline assessment, Müller-Riemenschneider et al (2008) identified only moderate evidence that behavioral interventions affected smoking. For interventions within the school context, evidence was inconclusive.…”
Section: Introductionmentioning
confidence: 98%
“…26) or smokers with substance use disorders (because of lack of evidence for differential effectiveness); (2) outcomes other than overall effect sizes (e.g. health inequalities 27, 28); (3) particular behavioural techniques, such as motivational interviewing 29; and (4) smoking initiation 30.…”
Section: Methodsmentioning
confidence: 99%
“…Critical reviews on youth smoking prevention programs indicated that school-based tobacco prevention interventions are effective in improving knowledge level, reducing smoking initiation and continuation in the short term (Baska, Straka, Baskova, & Madar, 2004;Dobbins, Decorby, Manske, & Goldblatt, 2008;Fray, 2009;Muller-Riemenschneider, Bockelbrink, Reinhold, Rasch, Greiner, & Willich, 2008;Peterson, Kealey, Mann, Marek, & Sarason, 2000;Skara & Sussman, 2003;Wiehe, Garrison, Christakis, Ebel, & Rivara, 2005). The researchers also found the intervention effectiveness has not been maintained for more than 3 years post-intervention and suggested continuous implementation of school-based tobacco prevention interventions (Dobbins et al, 2008).…”
Section: Introductionmentioning
confidence: 98%